Interferon Gamma Release Assay (QuantiFERON-TB Gold in Tube) in patients of sarcoidosis from a population with high prevalence of tuberculosis infection - Gupta, D.; Kumar, S.; Aggarwal, et al., A.N. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background and objective: Detecting latent tubercular infection (LTBI) in sarcoidosis has important treatment implications. Traditionally tuberculin skin test (TST) is relied upon for this purpose. However, sarcoidosis is known to produce tuberculin anergy, which is not affected by high prevalence of tuberculosis (TB) infection. Interferon gamma release assays (IGRAs) have a higher sensitivity and specificity for detecting Mycobacterium tuberculosis (MTB) infection than the conventional TST as they utilize antigens specific for MTB complex. However, there is limited data regarding the performance of these tests in sarcoidosis, particularly in a setting of high population prevalence of LTBI.Herein, we studied the utility of IGRAs in the diagnostic work up of patients with sarcoidosis. Patients and Methods: Prospectively enrolled, biopsy-confirmed, glucocorticoid naive cases of pulmonary sarcoidosis; pulmonary and extrapulmonary TB; and, healthy controls underwent TST using 0.1 mL (1 tuberculin unit) of purified protein derivative RT23, and IGRA using QuantiFERON-TBGold In Tube™ assay (QFT) in blood. For TST an induration ≥10 mm was taken as positive. QFT was performed and interpreted as per the manufacturer’s instructions. Results:We studied 38 patients with sarcoidosis (22 men, 16 women;mean age 42.5 years), 30 patients of TB (18 pulmonary, 12 extrapulmonary) and 30 healthy controls. Patients with sarcoidosis were more likely to have a negative TST compared to healthy controls (89.5% vs. 60%, p=0.004) or TB (89.5% vs. 23.3%, p<0.001). However, QFT positivity was not significantly different in sarcoidosis compared to controls (34.2% vs. 50%, p=0.19), but was higher in TB patients as compared to sarcoidosis (60% vs. 34.2%, p=0.03). Conclusions: There is anergy to tuberculin in sarcoidosis.However, the results of QFT are not similarly affected. QFT continues to remain positive in many patients with sarcoidosis, and thus may be more accurate to detect LTBI in these patients.